Nahed Hattar and the pan-Syrian origins of Jordanian nationalism - Sally Sharara; Tariq Tell (Revue des Mondes Musulmans et de la Méditerranée)
Generations of historians have discussed Jordanian history in terms of Great Power strategies or the dynastic ambitions of its Hashemite kings. This has led on to a persistent neglect of the social origins of the five Jordanian National Congresses (JNCs), as well as a persistent failure to consider their historical significance. The radical journalist Nahed Hattar articulated a Pan-Syrian variant of Jordanian waṭaniyya (a local patriotism centred on the post-colonial state) that placed an understanding of the social origins of the JNCs at the centre of a critique of the prevailing Hashemite-centred approaches to Jordanian history. A complete picture of Hattar’s writings on Jordanian nationalism requires detailed engagement with a vast corpus journalistic analysis, polemic and socio-political practice stretching back to his emergence as young opposition writer in the early 1980s. The following pages provide a preliminary sketch of Hattar’s ideas on the origins, evolution and content of Jordanian Nationalism during the Mandate years.